Design of passive SIW based mmWave devices for a six-port receiver-based sensor for automotive radar applications - Lui, Jin Jiang (2019)
This final year project contains designs and specifications based on the application of Substrate Integrated Waveguide (SIW) technology. Designs of components such as a six-port receiver, power divider leaky wave antenna and a planar circular disc monopole antenna are being used for the design of Automotive Radar Applications in the X-band (8 GHz to 12 GHz). To determine suitable designs to integrate the mentioned components and complete an automotive radar device that would detect gestures. The design included simulations of initial designs both individually and as a combined device. Through simulations, behaviors of the researched designs were identified. Appropriate alterations could be implemented to achieve desired results. Finally, the fabricated design underwent testing and troubleshooting. The first part of this work is about initial designs of the automotive radar device that included components such as Microstrip Patch Antenna, SIW based Line Waveguide, SIW based Directional Coupler, SIW based Power Divider to work at frequencies from around 8 GHz to 12 GHz as a prototype. This part included the simulation and analysis of the SIW based Six-port Receiver and a modification to the SIW based Power Divider. The second part of this work is about the integration of selected components such as the SIW based Power Divider, SIW based Six-port Receiver and a planar circular disc monopole antenna, operating at the X-band. This is to investigate the workability of the design for an automotive radar device, which can eventually be used for applications higher frequencies, to maximize the advantages that SIW provides.